Antifungal Properties of Methanol Extract from Gymnostoma nobile - Halimatun Saadiah, Mokhtar (Universiti Malaysia Sarawak (UNIMAS), 2014)
Natural durability is the ability of wood to prevent biological degradation and it is also been established that extractives influence the durability of wood. The presence of extractives will give natural durability of wood. The objectives of this study were to detennine the amount of methanol (MeOH) crude extract from G. nobile, and to evaluate the antifungal properties of MeOH extract from G. nobile. Solvent extraction by using MeOH was carried out. The antifungal properties were detennined in methanol extract using agar dilution method. The total MeOH crude extracts from G. nobile was 7.18%. MeOH crude extract from G. nobile were toxic to Trametes versicolor and Gleophyllum trabeum. It suggests that some compounds such as a-cadinol, T -cadinol, and T -muurolol are responsible towards antifungal activity extract from G. nobile.